Hidrolisis Mikroalga Tetraselmis Chuii Menjadi Glukosa Menggunakan Enzim Selulase - Novia Azzahra; Amun Amri; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Microalgae Tetraselmis chuii is one of biomass which has a potential to be converted into glucose that can be used as raw materials for bioethanol production and other intermediate products. One of the process was used for glucose production by using enzymatic hydrolysis with enzyme cellulase. The purpose of this researches were to study the influence of the hydrolysis time and optimum conditions at enzymatic hydrolysis. The sequances of this research were raw materials analysis, enzymatic hydrolysis, and glucose analysis. The process of the hydrolysis by dissolving microalgae in a buffer solution of sodium acetate pH 5,5, pH was re-set by way of added to acetic acid in microalgae mixture. After certain pH was achieved, an enzyme cellulase was added into microalgae mixture and stirred at 100 rpm, the temperature of 400C and varied hydrolysis time. Manipulated variable on this study were hydrolysis time, namely 15, 45, 75 hours at the ratio of algae/enzyme 1:0,03. The results was obtained namely glucose, with the highest concentration of 2,78 g/L on operating conditions for 45 hours at the rasio algae/ enzyme 1:0,03.Keywords: cellulase, glucose, hydrolysis, Tetraselmis chuii, time